Two-Dimensional Nanomaterials for Peripheral Nerve Engineering: Recent Advances and Potential Mechanisms - Yan, Zhiwen; Chen, Cheng; Rosso, Gonzalo; Qian, Yun; Fan, Cunyi (Frontiers in Bioengineering and Biotechnology, 2021)
Peripheral nerve tissues possess the ability to regenerate within artificial nerve scaffolds, however, despite the advance of biomaterials that support nerve regeneration, the functional nerve recovery remains unsatisfactory. Importantly, the incorporation of two-dimensional nanomaterials has shown to significantly improve the therapeutic effect of conventional nerve scaffolds. In this review, we examine whether two-dimensional nanomaterials facilitate angiogenesis and thereby promote peripheral nerve regeneration. First, we summarize the major events occurring after peripheral nerve injury. Second, we discuss that the application of two-dimensional nanomaterials for peripheral nerve regeneration strategies by facilitating the formation of new vessels. Then, we analyze the mechanism that the newly-formed capillaries directionally and metabolically support neuronal regeneration. Finally, we prospect that the two-dimensional nanomaterials should be a potential solution to long range peripheral nerve defect. To further enhance the therapeutic effects of two-dimensional nanomaterial, strategies which help remedy the energy deficiency after peripheral nerve injury could be a viable solution.